Theoretical Foundations of Web 2.0 for Teaching in Higher Education - David Enmanuel Michalón Dueñas; Cesar Gerardo Mejía Gallegos; Raúl Andrés Michalón Acosta; Raúl López Fernández; Diana E. Palmero Urquiza; María Beatriz García Saltos (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2017)
The avatars of Web 2.0 as a philosophy of educational teaching processes conception, have gained momentum in recent years. The objective of this paper is to characterize theoretically the Web 2.0 tools in terms of higher education context teaching. The study was done with documents socialized by experienced authors in the subject, coming from the region and the world. Web 2.0 has fundamental tools, such as massive and open online courses, ePortafolio, among others, which function as mediating elements in the teaching-learning process. It is concluded that the Web 2.0 supposes for higher education teachers a theoretical instrument, whose knowledge and application is reverted in university teaching quality.